2021
DOI: 10.2147/opth.s324977
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-Orbito-Cerebral-Mucormycosis During the COVID-19 Second Wave in 2021 – A Preliminary Report from a Single Hospital

Abstract: Purpose To list the clinico-epidemiological profile and possible risk factors of COVID-19 associated rhino-orbital-cerebral mucormycosis (CA-ROCM) patients presenting to a COVID dedicated hospital during the second wave of COVID-19 in India. Patients and Methods A cross-sectional, single-center study was done on 60 cases of probable CA-ROCM based on clinical features and supportive diagnostic nasal endoscopic findings and/or radiologic findings. Patients with recent or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
31
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 20 publications
13
31
3
Order By: Relevance
“…Out of the 37-biopsy samples, soft tissue invasion was noted in 59%, necrosis with no cellular response was noted in 43%, acute suppuration in 5% of cases (n=2), granulomatous inflammation in 11% of the cases. [27] The results of the present study closely match the above study with age, sex and predisposing factor being similar. Soft tissue invasion was seen in a higher percentage with 85% of the specimens, abscess formation in the present study was also noted in only two cases (3.33%).…”
Section: Discussionsupporting
confidence: 91%
“…Out of the 37-biopsy samples, soft tissue invasion was noted in 59%, necrosis with no cellular response was noted in 43%, acute suppuration in 5% of cases (n=2), granulomatous inflammation in 11% of the cases. [27] The results of the present study closely match the above study with age, sex and predisposing factor being similar. Soft tissue invasion was seen in a higher percentage with 85% of the specimens, abscess formation in the present study was also noted in only two cases (3.33%).…”
Section: Discussionsupporting
confidence: 91%
“…Our study was conducted with the aim of evaluating the patient profile and assessing the risk factors involved in secondary mucormycosis infection in COVID-19 patients over a period of 6 months. In this study, the majority were middle aged men (mean age-54.29±10.21, range 36-78 years) as also seen in the studies by Arora et al 13 where median age was 57 years; range 29-75 years and by Pakdel et al 14 where median age was 52 years; range 14-71 years. But as per a study by Bayram et al 15 , the mean age was 73.1±7.7 years (range 61-88 years).…”
Section: Discussionsupporting
confidence: 86%
“…The male to female ratio of our study group was 10.67:1. Male predominance in incidence was also seen studies by Patel et al 12 (323; 69.5%), Arora et al 13 (45; 75%), Pakdel et al 14 (66%), and Bayram et al 15 (9; 81.8%).…”
Section: Discussionsupporting
confidence: 66%
“…In our reviewed studies, the specific indications for retrobulbar injection of the drug were visual loss, signs of orbital apex involvement, and progression of the disease despite appropriate systemic medical and surgical treatments. 25 , 28 31 , 33 , 34 Similar indications were elucidated by Hirabayashi et al 19 In addition, we found that this route of the drug administration should be considered in earlier stages, especially in cases that are not good candidates for extensive surgical interventions (i.e., pediatrics and admitted patients to an intensive care unit, ICU). 29 , 31 In the COVID-19 era, many cases are admitted to the ICU and, therefore, are not candidates with favorable outcomes following surgical interventions (including paranasal sinuses and orbital debridements).…”
Section: Discussionsupporting
confidence: 73%